Systematic Literature Review (SLR): Analysis of Factors Influencing Interest in Opening A Hajj Savings Account at Bank Syariah Indonesia - Fadila Afri Rahmawati; Mochammad Andre Agustianto (Program Studi Ekonomi Syariah, FEBI UIN Datokarama Palu, 2024)
This study aims to analyze the factors that can influence a person's interest in saving for Hajj at Bank Syariah Indonesia. The analysis of these factors can later become a reference for Bank Syariah Indonesia to carry out marketing strategies appropriately and efficiently. This study uses a qualitative method with a Systematic Literature Review using the Publish or Perish application to analyze various journals following the researcher's topic on Google Scholar. Journals are selected using the Systematic Search and Screening method through a systematic search strategy process, effective use of keywords, application of inclusion and exclusion criteria, and a gradual screening process to select the most relevant articles. The analysis results show that promotion, customer service, and religiosity are considered more significant in influencing a person's interest in saving for Hajj. In addition, several other factors influence a person's interest in opening a hajj savings account at Bank Syariah Indonesia. These findings provide insight or can be used as evaluation material to develop appropriate strategies for Bank Syariah Indonesia to increase public interest in opening hajj savings.